Comprehensive meta-analysis of anti-BCMA chimeric antigen receptor T-cell therapy in relapsed or refractory multiple myeloma. (1st January 2021) - Zhang, Lina; Shen, Xuxing; Yu, Wenjun; Li, Jing; Zhang, Jue; Zhang, Run; Li, Jianyong; Chen, Lijuan
Abstract: Background: Chimeric antigen receptor (CAR) T-cell therapy shows impressive results in clinical trials. We conducted a meta-analysis based on the most recent data to systematically describe the efficacy and safety of anti-BCMA CAR T therapy for patients with relapsed or refractory multiple myeloma (R/R MM). Methods: PubMed, Embase, Web of Science, Cochrane library, ClinicalTrials.gov, China Biology Medicine disc (CBM disc) and Wanfang Data were searched on 8 November 2020. Registration number of PROSPERO was CRD42020219127. Results: From 763 articles, we identified 22 appropriate studies with 681 patients. The pooled overall response rate (ORR) was 85.2% (95%CI 0.797–0.910), complete response rate (CRR) was 47.0% (95%CI 0.378–0.583), and minimal residual disease (MRD) negativity rate was 97.8% (95%CI 0.935–1.022). The pooled incidence of grade 3–4 cytokine release syndrome was 6.6% (95%CI 0.036–0.096) and neurotoxicity was 2.2% (95%CI 0.006–0.038). The median progression-free survival (PFS) was 14.0 months and median overall survival (OS) was 24.0 months. Subgroup analysis showed dual epitope-binding CAR T cells achieved the best therapy outcomes and humanized CAR T cells had the best safety profile. Patients who were older, heavily pre-treated or received lower dose of CAR T cells had worse ORR. There was no significant difference in ORR, CRR and PFS between patients with and without high-risk cytogenetic features. The PFS and CRR of non-extramedullary disease (EMD) group was superior to those of EMD group. Conclusion: Anti-BCMA CAR T therapy is effective and safe for patients with R/R MM. It can improve the prognosis of patients with high-risk cytogenetic features while the prognosis of patients with EMD remains poor. Moreover, patients are likely to benefit from an earlier use of CAR T therapy and human-derived CAR T cells have obvious advantages based on the existing data.